The Didactic Values in The Novel Of 9 Summers 10 Autumns - Rahmita Sari; Surastina Surastina; Akhmad Sutiyono; Tri Riya Anggraini (IJLHE: International Journal of Language, Humanities, and Education, 2018)
This study aims to describe the didactic values ​​of the novel "9 Summers 10 Autumns" and to describe aspects of the novel "9 Summers 10 Autumns". The authors use the analytical method – description to achieve the research objectives above, which is to decompose the meaning of the data in words instead of numbers. This method describes the facts that exist then, followed by analytical ways. In the description method, the novel is used as the object of research analyzed and defined by the research objectives. Based on research in the novel "9 Summers 10 Autumns" by Iwan Setyawan, there are didactic values ​​, including; religious education, moral education, and social education.